(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Attachment styles are the result of the first attachment relationships between a child and a particular person, since during the attachment relationship mental models are formed, which influence personal development and behavior towards interpersonal relationships over time. long of life. The objective of the research consisted in evaluating and interpreting the attachment style that predominates in women from the State of Tabasco between 40 and 50 years of age and highlighting the importance of the attachment style in the development of the personality of women. The CAMIR Questionnaire was applied, which measures attachment styles and mental representations of attachment, past, present, and family functioning. The role of women in Tabasco is related to the type of attachment that they have lived since childhood, the experience they have had with their caregivers has a fundamental role in the subsequent ability to establish affective bonds, since it is important that the girl can depend on her parents. attachment figures and that they can contain and protect her when she needs it.